Brave new creatures : a comparative study of Mary Shelley's Frankenstein and the creatures of the new millenium - Gastaldi, Sandra M.M (2015)
This thesis intends to analyse Mary Shelley‘s creature in her novel Frankenstein, and how the creation of this creature may have adumbrated the birth of present creatures—clones, genomes,1 Artificial Intelligence (AI) creatures like robots and androids—that spring from the latest technological and scientific advances. The Promethean ambition to play God in order to create life persists, and it is present today more than ever before. Within the frame of Cultural Studies and Intertextuality, I dwell upon the similarities and the differences between Mary Shelley´s creature and these ―brave new creatures.‖ Mary Shelley´s Frankenstein was provided with spiritual life and human characteristics such as suffering for love, neglect, and scorn, but the idea of the human as matter was already present in Shelley´s novel: Frankenstein was an ensemble of pieces of corpses. In this thesis I explore to which extent and how the creatures of the new millennium depart from or are similar to the original creature Frankenstein. In Brave New World (1932) Aldous Huxley had already speculated about genetic engineering, test tube babies, and a materialistic conception of human life. Today science and technology challenge us with a future new human race as the cases presented in this study. In view of all this, to ponder what the future may bring about is worth a try.